A Theology of Animality: Review of Eric Daryl Meyer, Inner Animalities: Theology and the End of the Human - Beverly, Jared (Humanimalia, 2019)
Eric Daryl Meyer, Inner Animalities: Theology and the End of the Human. Groundworks: Ecolological Issues in Philosophy and Theology. New York: Fordham University Press, 2018. 224 pp. $115.00 hc; $32.00 pb; 31.99 e-book.